Conservative Management of Separated Instrument in Root Canal by Bypassing Technique: a Case Report - Singh, Amit Kumar (Journal of BP Koirala Institute of Health Sciences, 2023)
Separated instruments in root canal treatment are an unfortunate occurrence that can happen during the procedure. These instruments can become lodged in the canal, making it challenging to complete the treatment adequately. However, it is possible to manage this situation by bypassing the separated instrument. There are two primary ways to manage a separated instrument: bypassing and retrieval. Retrieval of a separated instrument is a challenging task that requires specialized tools and skills. Therefore, bypassing the separated instrument is often the conservative and less invasive method. This case report describes the conservative approach (bypass technique) to deal with broken instruments with minimum armamentaria. Furthermore, the bypassing technique does not carry much risk since it does not mandate significant removal of dentin structure.